SCAFFOLDING METHOD FOR TEACHING SPEAKING TO INDONESIAN MIGRANT WORKERS - Sholakhuddin, Faris; Puspita Kirana, Dhinuk (University of Darussalam Gontor, 2024)
Indonesian migrant workers in Penang, Malaysia, face significant challenges in acquiring English speaking skills, primarily due to their lack of self-confidence, limited speaking skill, and insufficient opportunities for practice. This research examines the application of the scaffolding method by teachers to bridge the gap between learners’ current skills and their potential for growth in English speaking proficiency. Specifically, it analyzes the use of scaffolding in teaching speaking skills to Indonesian migrant workers at the English Academy Bengkulu Malaysia. Employing a descriptive qualitative method, the study involved the manager and two teachers selected through purposive sampling. Data collection methods included observation, interviews, and documentation analysis. The scaffolding method was implemented in four stages: assistance provided by others, assistance provided by the self, internalization, and de-automatization. In the first stage, teachers utilized affective, analytical, and social scaffolding techniques. During the second stage, students practiced speaking independently, with teachers emphasizing confidence by overlooking minor errors. The third stage, internalization, involved